From Insult to Injury: How Disputes Begin and Escalate among Adolescents and Young Adults in Medellin, Colombia - Duque, Luis F.; Montoya, Nilton E. (International Journal of Criminology and Sociology, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> This article aims to contribute to the understanding of circumstances, causes of initiation, and process of escalation of physical disputes or fights resulting in physical injury. We analyzed data from a case-control study of perpetrators of violence between the ages of 15 to 24 (n=373) in the city of Medellín, Colombia. The findings show that 89% of conflicts resulting in injury took place in public places and most often involved males (78%). Six percent involved the consumption of alcohol, 20% reported having used illicit drugs before the initiation of the confrontation. Circa 50% of disputes began because of verbal aggression. Alcohol consumption was found to be associated with verbal aggression towards a friend or companion but not to other circumstances that start disputes. Drug use was not associated with the initiation of disputes. In 18.5% of the cases, a weapon was used while 5% of these disputes ended in a homicide. In none of the cases in which homicide was the outcome was there bystander intervention. In contrast, homicide did not result in the cases in which bystanders intervened.